2018
DOI: 10.1039/c8ra06982d
|View full text |Cite
|
Sign up to set email alerts
|

Improved carrier injection of AlGaN-based deep ultraviolet light emitting diodes with graded superlattice electron blocking layers

Abstract: DUV-LEDs with a single EBL, graded EBL, and graded superlattice EBL were demonstrated using the high-temperature metal organic chemical vapor deposition system. A DUV-LED with a GSL-EBL showed improved carrier injection into the multi-quantum well region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…In addition, it is found that a portion of the electrons were stored at the interface of LQB and p‐EBL (called “parasitic electron reservoir [PER]” and marked by the red arrow) in sample B, which is caused by the downward bent energy band in the LQB layer. [ 30,31 ] These electrons will be eventually consumed by nonradiative recombination process. Furthermore, according to the relationship between the effective conduction band barrier height ( ϕ c ) and the electron concentration ( n ) at the interface, it can be expressed as follows [ 12 ] ϕnormalC=ΔEnormalCkT·ln(nNnormalC)…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is found that a portion of the electrons were stored at the interface of LQB and p‐EBL (called “parasitic electron reservoir [PER]” and marked by the red arrow) in sample B, which is caused by the downward bent energy band in the LQB layer. [ 30,31 ] These electrons will be eventually consumed by nonradiative recombination process. Furthermore, according to the relationship between the effective conduction band barrier height ( ϕ c ) and the electron concentration ( n ) at the interface, it can be expressed as follows [ 12 ] ϕnormalC=ΔEnormalCkT·ln(nNnormalC)…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] To solve these problems and improve the optoelectronic performance of DUV‐LEDs, scientifically designed EBL and LQB epitaxial structures are necessary. To alleviate electron leakage without blocking hole injection, some unique epitaxial structures have been proposed, such as w‐shaped EBL, [ 24 ] InAlGaN/AlGaN EBL, [ 16 ] double‐peak superlattice EBL, [ 25 ] graded superlattice EBL, [ 26 ] composition‐graded AlGaN LQB, [ 27 ] and two‐step graded AlGaN LQB. [ 28 ] Except for the optimization of EBL and LQB structures, many researchers have focused on the polarization doping, [ 29 ] tunneling junctions, [ 30 ] and short‐period superlattice [ 31 ] hole injection layers (HIL) to enhance the hole injection efficiency of p‐type layers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been demonstrated that multibarrier EBL in DUV‐LEDs can effectively improve the carrier injection efficiency. [ 26 ] However, seeking for reasonable EBL and LQB to improve the quantum efficiency of DUV‐LEDs deserves further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the hole activation and hole injection into the active region, different band‐engineered superlattice (SL) structures have been adopted; i.e., single‐/double‐step‐graded SL structure in the EBL [ 11,12 ] and SL hole injection layer (HIL). [ 13 ] A SL structure has been demonstrated for improved hole activation efficiency by reducing the Mg activation energy.…”
Section: Introductionmentioning
confidence: 99%